Characterization of a monoclonal antibody that binds to both gp120 and gp41. (December 2018) - Zheng, Hao; Tang, Jiansong; Lu, Shiqiang; Qian, Qian; Liu, Wan; Yang, Zheng; Liu, Bing; Long, Long; Ding, Xiaomei; Lin, Pinya; Pun, Johnny; Wong, Kiana; et al.
Aim: AIDS has become a global pandemic. Characterization of broadly HIV-1-neutralizing antibodies (bnAbs) may facilitate the vaccine design.Methods & materials: Recombinant antibody library construction provides a resourceful way of monoclonal antibody screening and isolation against HIV-1.Results: In this study, we screened a novel human monoclonal antibody, named 2B8, which can bind both the gp120 and gp41 subunits of the HIV-1 envelope glycoprotein (Env). 2B8 did not bind to the CD4 binding site mutant, gp120 D368R, suggesting that the 2B8 epitope is conformational and overlaps the CD4 binding site on gp120. 2B8 neutralized 50% of the HIV-1 cell line-based pseudo virus isolates tested.Conclusion: The further study of its novel epitope may reveal the new mechanism of neutralization and assist the design of vaccine immunogens against HIV-1.